4,4′-methylenebis(2-chloroaniline) induces chromosome aneuploidy associated with premature chromatid separation in mammalian cells: A possible carcinogenic mechanism - Saho Kobayashi; Hiroki Kashiwagi; Kenichi Kobayashi; Masaoki Kohzaki (Ecotoxicology and Environmental Safety)
In Japan, several workers were diagnosed with bladder cancer 10–40 years after exposure to 4,4′-methylenebis(2-chloroaniline) (MOCA), mainly through the skin. MOCA also induces bladder cancer in dogs and nonbladder (breast, liver, lung) cancers in rodents. MOCA with S9 fractions contains mutagenic metabolites after catalysis by N-acetyl transferase (NAT). Similar to benzidine and ortho-toluidine, MOCA is classified as a group 1 carcinogen by the IARC. However, since dogs lack NAT, the common mechanism underlying bladder cancer development across mammalian species remains elusive. We used human liver HepG2, lung A549, breast MCF7, bladder T24, 5637 cells; mouse lung LLC, breast TS/A, and bladder MBT-2 cells; and rat bladder NBT-T2 cells to analyze the mitotic effects of aromatic amines (benzidine, ortho-toluidine, 2-chloroaniline, and 4,4′-methylenedianiline) to elucidate the common mechanism underlying MOCA-induced cancer in mammals. The effects of MOCA metabolites were assessed in liver S9 fractions. In vivo, male F344 rats were administered MOCA (0, 60, or 120 mg/kg/day) percutaneously three times a week for 4 weeks to mimic human exposure, and MOCA-induced chromosomal instability in lung and bladder cells was evaluated one month later. Compared with other aromatic amines or S9-metabolized MOCA, MOCA significantly increased the mitotic index in all the examined cell lines (p < 0.0001) and markedly induced cohesion defects in human and rat cells (p < 0.036). Rats repeatedly exposed to MOCA exhibited dose-dependent chromosome aneuploidies in lung- and bladder-derived cells. Thus, MOCA induces chromosome aneuploidy via cohesion defects independent of hepatic metabolism, contributing to mammalian carcinogenesis in vivo.